The role of aryl hydrocarbon receptor in correlation to IL-17 level in non-allergic asthma - Aliaa Abood; Shereen Al-Ali; Iqbal Abdul Aziz; Ziad T.Malgoth (International Journal of Medical Toxicology and Legal Medicine, 2024)
Asthma is a heterogenic chronic disease of the airways. It also classified as allergic and non-allergic asthma, which its mechanism based on the action of Th17 cell and affected by other risk factors such as body mass index (BMI). The aryl hydrocarbon receptor (Ahr) is a xenobiotic agent which activated by exogenous and endogenous ligands, and it has been considered to be a regulator of both toxic and carcinogenic responses to environmental pollutants. Recently, it has been linked to several immune disorders including asthma. The aim of the study the role of Ahr in correlation to IL-17 non-allergic asthma.Blood from non-allergic asthma patients and aged matched healthy controls were collected, complete blood count (CBC) was performed on each sample and the serum level of IL-17 and Ahr were estimated by enzyme linked immunosorbent assay (ELISA). The majority of AS patients were obese (34.3%). The current findings of the present study revealed a significant elevation (p=0.00001) of IL-17 level in AS group in compare to HC group(22.59±3.7 and 3.14±0.4 ul/ml, respectively).The level of Ahr showed a significant elevation (p=0.025) in AS group in compare to HC group (46.91±5.9 and 21.58± 4.2 ul/ml, respectively).A strong significant and positive correlation was found betweenIL-17 and AhR level in asthma patients (R2 = 0.75, p=0.00) in compare to no correlation found between them in healthy controls (R2 = -0.5, p=0.054).The results of the receiver operating characteristic (ROC) curve for the two parameters in the present study showed that IL-17 gave an excellent performance in the ROC with AUC =0.961 followed by the Ahr with AUC= 0.704.In conclusion, in non-allergic asthma, Ahr correlates positively with IL-17 suggesting a significant role of Ahr in non-allergic asthma and the possibility of a new therapeutic agent to treat non-allergic asthma.